Software Quality. Increasing Value in Software and Systems Development 5th International Conference, SWQD 2013, Vienna, Austria, January 15-17, 2013. Proceedings - Winkler, Dietmar; Biffl, Stefan; Bergsmann, Johannes; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 5th Software Quality Days Conference (SWQD) held in Vienna, Austria, in January 2013. This professional symposium and conference offers a range of comprehensive and valuable opportunities for advanced professional training, new ideas, and networking with a series of keynote speeches, professional lectures, exhibits, and tutorials. The seven scientific full papers accepted for SWQD were each peer-reviewed by three or more reviewers and selected out of 18 high-quality submissions. Further, two keynotes and six short papers on promising research directions were also presented and included in order to spark discussions between researchers and practitioners. The papers are organized into topical sections on risk management; software and systems testing; test processes; model-based development; and process improvement and measurement.
Keynotes -- Software Quality: From Requirements to Architecture -- The Consortium for IT Software Quality (CISQ) -- Risk Management -- Experiences and Challenges of Introducing Risk-Based Testing in an Industrial Project -- Project Progress and Risk Monitoring in Automation Systems Engineering -- Software and Systems Testing -- WebMate: Generating Test Cases for Web 2.0 -- Testing Web Services in the Cloud -- Model-Based Strategies for Reducing the Complexity of Statistically Generated Test Suites -- Hazard Analysis for Technical Systems -- Test Processes -- Using Defect Taxonomies to Improve the Maturity of the System Test Process: Results from an Industrial Case Study -- Model-Based Development -- A Transformation of Business Process Models into Software-Executable Models Using MDA -- Aligning Domain-Related Models for Creating Context for Software Product Design -- Process Improvement and Measurement -- Mapping CMMI and RUP Process Frameworks for the Context of Elaborating Software Project Proposals -- Development and Evaluation of Systems Engineering Strategies: An Assessment-Based Approach -- Improving Completeness of Measurement Systems for Monitoring Software Development Workflows -- Exploiting Natural Language Definitions and (Legacy) Data for Facilitating Agreement Processes.
Keywords: Computer science; Software engineering; Information Systems; Computer Science; Software Engineering; Management of Computing and Information Systems; Project Management